Cerebral small vessel disease affects white matter microstructure in mild cognitive impairment. Issue 6 (23rd September 2013) - Papma, Janne M.; de Groot, Marius; de Koning, Inge; Mattace‐Raso, Francesco U.; van der Lugt, Aad; Vernooij, Meike W.; Niessen, Wiro J.; van Swieten, John C.; Koudstaal, Peter J.; Prins, Niels D.; Smits, Marion
Abstract Microstructural white matter deterioration is a frequent finding in mild cognitive impairment (MCI), potentially underlying default mode network (DMN) dysfunctioning. Thus far, microstructural damage in MCI has been attributed to Alzheimer's disease pathophysiology. A cerebrovascular role, in particular the role of cerebral small vessel disease (CSVD), received less interest. Here, we used diffusion tensor imaging (DTI) to examine the role of CSVD in microstructural deterioration within the normal appearing white matter (NAWM) in MCI. MCI patients were subdivided into those with (n = 20) and without (n = 31) macrostructural CSVD evidence on MRI. Using TBSS we performed microstructural integrity comparisons within the whole brain NAWM. Secondly, we segmented white matter tracts interconnecting DMN brain regions by means of automated tractography segmentation. We used NAWM DTI measures from these tracts as dependent variables in a stepwise‐linear regression analysis, with structural and demographical predictors. Our results indicated microstructural deterioration within the anterior corpus callosum, internal and external capsule and periventricular white matter in MCI patients with CSVD, while in MCI patients without CSVD, deterioration was restricted to the right perforant path, a tract along the hippocampus. Within the full cohort of MCI patients, microstructure within the NAWM of the DMN fiber tracts was affected by the presence of CSVD. Within the cingulum along the hippocampal cortex we found a relationship between microstructural integrity and ipsilateral hippocampal volume and the extent of white matter hyperintensity. In conclusion, we found evidence of CSVD‐related microstructural damage in fiber tracts subserving the DMN in MCI. Hum Brain Mapp 35:2836–2851, 2014. © 2013 Wiley Periodicals, Inc.